Correlation of spleen metabolism assessed by 18F-FDG PET with serum interleukin-2 receptor levels and other biomarkers in patients with untreated sarcoidosis. Issue 3 (March 2016) - Kalkanis, Alexandros; Kalkanis, Dimitrios; Drougas, Dimitrios; Vavougios, George D.; Datseris, Ioannis; Judson, Marc A.; Georgiou, Evangelos
Abstract : Background: The objective of our study was to assess the possible relationship between splenic F-18-fluorodeoxyglucose ( 18 F-FDG) uptake and other established biochemical markers of sarcoidosis activity. Patients and methods: Thirty treatment-naive sarcoidosis patients were prospectively enrolled in this study. They underwent biochemical laboratory tests, including serum interleukin-2 receptor (sIL-2R), serum C-reactive protein, serum angiotensin-I converting enzyme, and 24-h urine calcium levels, and a whole-body combined 18 F-FDG PET/computed tomography (PET/CT) scan as a part of an ongoing study at our institute. These biomarkers were statistically compared in these patients. Results: A statistically significant linear dependence was detected between sIL-2R and log-transformed spleen-average standard uptake value (SUVavg ) ( R 2 =0.488, P <0.0001) and log-transformed spleen-maximum standard uptake value (SUVmax ) ( R 2 =0.490, P <0.0001). sIL-2R levels and splenic size correlated linearly (Pearson's r =0.373, P =0.042). Multivariate linear regression analysis revealed that this correlation remained significant after age and sex adjustment ( β =0.001, SE=0.001, P =0.024). No statistically significant associations were detected between (a) any two serum biomarkers or (b) between spleen-SUV measurements and any serum biomarker other than sIL-2R. Conclusion: Our analysis revealed an association between sIL-2R levels and spleen 18 F-FDG uptake and size, whereas all other serum biomarkers were not significantly associated with each other or with PET 18 F-FDG uptake. Our results suggest that splenic inflammation may be related to the systemic inflammatory response in sarcoidosis that may be associated with elevated sIL-2R levels.